Research Trends in Problem-Solving Skills within Science Learning: A Bibliometric Analysis Using the Scopus Database (2002-2026) - Misbah Misbah; Surya Haryandi; Ahmad Bakharzi Hakam; Qamariah Qamariah; Erwina Oktavianty (Tarbiyah : Jurnal Ilmiah Kependidikan, 2026)
Research regarding problem-solving skills in science learning continues to expand, necessitating the mapping of publication trends on this topic. This study employed a bibliometric analysis designed to map research trends concerning problem-solving skills within science learning utilizing the Scopus database from 2002 to 2026. Data were gathered from Scopus export results on March 25, 2026, yielding 65 relevant documents. The analysis focused on the chronological development of annual publications, institutional affiliations, contributing countries, publication venues, author prominence based on citations and document counts, and keyword clustering visualized through the VOSviewer approach. The findings indicated that publications initially emerged in 2002 and exhibited an upward trend from 2018 onward, reaching a peak of 10 documents in 2025. Keyword co-occurrence analysis revealed seven primary clusters centered on problem-solving skills, science learning, students, education computing, learning systems, and problem-based learning. These findings demonstrate that research into problem-solving skills within science learning is evolving toward innovative instruction, technology integration, and the reinforcement of 21st-century skills. Theoretically, this study contributes to mapping the structure of knowledge, while practically providing guidance for researchers, educators, and curriculum developers in defining future research agendas and instructional practices in science education. This study serves as a bibliometric mapping spanning from the inception of publication until the year 2026 using the Scopus database, executed through a selection process adhering to the PRISMA protocol.